(untitled) (Fiep Bulletin - online, 2013)
Flexibility may be understood as the maximal articular range done to perform a movement. In persons with cerebral spastic palsy, there is a restriction in the movement owing to muscle hyper tonicity. Based upon this information, the aim of this study was to verify if specific flexibility training for shoulder joint could result in improvement in articular mobility, during the aerial phase of the chest stroke in crawl-style swimming. The study took into consideration that the shoulder plays a greatest role in optimizing the chest stroke. The sample was composed by 2 swimmers tetraparethic and spastic, with the greatest lesion in the legs. They were training swimming for at least 6 month, one of them a female (swimmer A) an the other, a male (swimmer B). Data were collected in a period of 3 month, and measurements of the angles of the shoulder in abduction, flexion and internal rotation were performed with a fleximeter. Analysis of the performance (quality of the breast stroke) and the angles before and after treatment allowed a conclusion that the intervention was successful. Swimmer A showed increase in flexibility of 3,87% in right and of 3,86% in the left shoulder. Swimmer B showed increase in flexibility of 5,24% in the right and 5,71% in the left shoulder. Besides that, they related reduction of pain produced by the shortening of the muscles, witch accounted for a better performance in routinely daily movements.